Institutional and Legal Problems of Economic Safety - STEPANYAN, Tamara M.; OKHOTNIKOV, Ilya V.; SPEKTOR, Asiya A.; YASHKOVA, Natalya V.; TUMANOV, Eldar V. (Journal of Advanced Research in Law and Economics, 2019)
Study of the main institutional and legal problems of economic security. The methodological basis for the study of the problem were the following methods: theoretical (analysis and generalization of scientific literature and sources, analysis of educational materials), formal-logical, system-structural, technical-legal, analysis, synthesis, abstraction, comparison, induction, deduction, etc. The importance of institutional and legal problems of economic security. The analysis of scientific sources related to the concept of economic security of the state in national and international terms. Emphasis is placed on the importance of the problem of the impact of globalization and its ‘derivatives’ on economic security as an institutional category. The positive and negative potential of digitalization as a factor of influence on economic security through the prism of the digital economy is revealed in detail. In this context, the analysis of the practice of solving institutional and legal problems of economic security of the EAEU member States in order to successfully implement the Eurasian economic integration. The strategic objectives of Russia in this project are shown, recommendations on the formation of a strong institutional and legal model of economic security of the country are given.